153k views
3 votes
If f(x)=(x+3)³+4
let g(x)=f(x+1)-2
find when g(x)=12

User JDesigns
by
5.9k points

1 Answer

5 votes

Answer:


x=\sqrt[3]{10}-2

Explanation:

The composite function (f(x+1)) is moved in the x-axis by -1, you know this by solving x+1=0.

The equivalent expresion for f(x+1) is


f(x+1)= (x-1+3)^(3)+4


f(x+1)=(x+2)^(3)+ 4

Eval the above expression in g(x)


g(x)=(x+2)^(3)+4-2

We must find x that gives g(x)=12

The equation is the following


12=(x+2)^(3)+2

Grouping terms>


(x+2)^(3) =10

To solve for x, must apply cubic root in both sides of equation:


\sqrt[3]{(x+2)^(3) } =\sqrt[3]{10}

it then turns in the following>


x+2=\sqrt[3]{10}\\

Giving the stated answer

User Arivero
by
6.7k points